G383(P) A Rare case of arrested childhood cerebral x-linked adrenoleukodystrophy with adrenal insufficiency. (24th May 2017) - Doherty, L; Warren, C; Kumar, Y; Crowne, E; Likeman, M; Steward, C
Abstract : Aim: To present a new phenotype of arrested cerebral X-linked adrenoleukodystrophy (X-ALD) with adrenal insufficiency. Method: Retrospective case note analysis. Results: 13 year old boy diagnosed with X-ALD who presented with features of Addison's disease (lethargy and skin pigmentation). Diagnosis was hastened by the identification of X-ALD in his 10 year old brother who presented typically with deterioration in cognitive and behavioral skills without features of adrenal insufficiency. MRI brain at presentation revealed confluent changes in peritrigonal white matter and splenium of the corpus callosum bilaterally with no enhancement – consistent with arrested cerebral ALD. Serum very long chain fatty acids (VLCFA) were significantly elevated confirming the diagnosis. MRI four months after presentation showed no change from the previous scan. To date, the patient has not exhibited any clinical neurodegeneration and is performing above average in mainstream school.Seven distinct phenotypes of ALD affecting males have been described: childhood cerebral, adolescent cerebral, adult cerebral, adrenomyeloneuropathy with and without cerebral disease, 'Addison's only' and asymptomatic forms. 1 There is limited existing literature regarding cases of arrested ALD. A 1996 German case study describes 3 boys diagnosed with ALD between the ages of 5 and 11 who initially showed typical rapid neurodegeneration before cessation of progression of leukodystrophy and stabilisation of symptoms. 2 However, unlike our case these individuals were all left with impaired cognitive capacity and were unable to remain in mainstream education. The resting range of IQ scores for these individuals ranged from 40–75. 2 A further UK case study of a 26 year old man with auditory processing difficulties since childhood presented when his brother was diagnosed with advanced ALD. MRI brain showed typical confluent hyperintense changes in the occipitoparietal regions involving auditory tracts. There was no evidence of further neurodegeneration for the 7 years of follow up. 3 This contrasts with our case who has a significantly abnormal MRI, no deterioration of cognitive function but abnormal adrenal function. Conclusion: We propose that this case may represent a new phenotype of adrenoleukodystrophy in children – arrested asymptomatic cerebral leukodystrophy with associated adrenal insufficiency. References: Engelen M, Kemp S, de Visser M, van Geel B, Wanders R, Aubourg P, Pull-The B. X-linked adrenoleukodystrophy (X-ALD): clinical presentation and guidelines for follow-up and management. Orphanet Journal of Rare Diseases 2012, 7:51. Korenke GC, Pouwels P, Frahm J, Hunneman D, Stoeckler S, Krasemann E, Jost W, Hanefeld F. Arrested cerebral adrenoleukodystophy: a clinical and proton magnetic resonance spectrometry study in three patients. Pediatric neurology, 1996;15:103–107. Bamiou D, Davies R, Jones S, Musiek F, Rudge P, Stevens J, Luxon L. An unusual case of X-linked adrenoleukodystrophy with auditory processing difficulties as the first and sole clinical manifestation. J Am Acad Audiol, 2004; 15: 152–160.